Coping in sport: A systematic review - Nicholls, A. R.; Polman, R. C. J. (Journal of Sports Sciences, 2007)
The aim of this paper was to systematically review the literature on coping in sport, examining evidence for both the trait and process perspectives, the types of coping strategies used by athletes, gender differences, age-related differences, and coping effectiveness. A comprehensive literature search of SPORTdiscus, PsychLIT, and PsychINFO in November 2004 yielded 64 studies spanning 16 years (1988 - 2004). The results indicated that athletes use a variety of coping strategies. Forty-six papers supported or adopted the process perspective (Lazarus, 1999; Lazarus & Folkman, 1984). There were also gender and age-related differences. Evidence was found to support three of the different models of coping effectiveness (goodness-of-fit approach, choice of coping strategy, and automacity). Based on this evidence, future research should address some of the methodological and measurement limitations of the sport psychology coping literature. In particular, prospective research designs that minimize the time delay between recall and the stressful experience are required to assess how coping changes over time. More attention to developmental issues to guide the formulation of sport-specific models to enhance our theoretical understanding is also required. Finally, coping effectiveness should be examined both in the short and long term, as a greater understanding of coping effectiveness has the potentional to make a significant impact on applied practice.